2017
DOI: 10.1186/s12915-017-0400-8
|View full text |Cite
|
Sign up to set email alerts
|

Silicanin-1 is a conserved diatom membrane protein involved in silica biomineralization

Abstract: BackgroundBiological mineral formation (biomineralization) proceeds in specialized compartments often bounded by a lipid bilayer membrane. Currently, the role of membranes in biomineralization is hardly understood.ResultsInvestigating biomineralization of SiO2 (silica) in diatoms we identified Silicanin-1 (Sin1) as a conserved diatom membrane protein present in silica deposition vesicles (SDVs) of Thalassiosira pseudonana. Fluorescence microscopy of GFP-tagged Sin1 enabled, for the first time, to follow the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
0
21

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 48 publications
(66 reference statements)
10
90
0
21
Order By: Relevance
“…At the end of R1, R3, and R5, we found an RXL domain. This domain acts as recognition site for unknown proteases that cleave at the C-terminus of the leucine residue of the RXL domain in many bio-silica associated proteins in diatoms (Kröger et al ., 1999; Wenzl et al ., 2008; Scheffel et al ., 2011; Kotzsch et al ., 2017). Despite these common features, Slp1 does not show sequence similarity with any protein known to be involved in bio-mineralization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of R1, R3, and R5, we found an RXL domain. This domain acts as recognition site for unknown proteases that cleave at the C-terminus of the leucine residue of the RXL domain in many bio-silica associated proteins in diatoms (Kröger et al ., 1999; Wenzl et al ., 2008; Scheffel et al ., 2011; Kotzsch et al ., 2017). Despite these common features, Slp1 does not show sequence similarity with any protein known to be involved in bio-mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…Binding of anti-Peptide-1 antibody in the boundary of dead silica cells of mature leaves suggests that as Slp1 templates the silica precipitation, it is caught inside the silica structure. Silicanin-1, a biosilica associated protein from T. pseudonana gets embedded inside biosilica structure and is accessible to anti-silicanin-1 antibody (Kotzsch et al ., 2017). Similarly, anti-Peptide-1 antibody may also have access to the epitope remains on the surface of the deposited silica in silica cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, we observed downregulation of genes known to be important for silica cell wall formation after treatment with SIP ( Figure 3A). These include two silicic acid transporters: membrane proteins that are involved in the uptake of silicic acid from the environment 52 ; two silicanins: proteins embedded in the SDV membrane 53 ; as well as four frustulins: proteins which are found in the organic casing surrounding the cell wall 54 . Moreover, four genes making up various subunits of V-type ATPase complexes were significantly downregulated in both species upon treatment with SIP.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed several key proteins and components closely associated with diatom cell-wall formation, including cingulins (Scheffel et al, 2011), silacidins (Wenzl et al, 2008), silaffins (Kr€ oger et al, 1999), silicanin (Kotzsch et al, 2017), and long-chain polyamines (Kr€ oger et al, 1999(Kr€ oger et al, , 2000. In particular, cingulins, which were initially discovered in the model diatom species T. pseudonana (Scheffel et al, 2011), are components associated with the girdle band silicification.…”
Section: Introductionmentioning
confidence: 99%